Analytical Study of Portal Vein Thrombosis: Risk Factors and Clinical Characteristics (Latakia University Journal -Medical Sciences Series, 2024)
Background: Portal vein thrombosis (PVT) is an important and poorly studied condition with a poorly defined natural history.The diagnosis of portal vein thrombosis has increased in recent years due to the availability of modern imaging techniques.The main aim of this study was to determine the risk factors, symptoms, and clinical signs of PVT. Methods: The study included 30 patients diagnosed with portal vein thrombosis by Doppler ultrasound or CT scan from patients attending Tishreen University Hospital from January 2023 to January 2024. Results: A single risk factor for portal vein thrombosis was found in 70% of patients, two factors were present in 10%, and PVT was idiopathic in 20%.Abdominal malignancies were the most common risk factor (36.6%) and abdominal pain was the most common manifestation (53.3%).The percentage of acute thrombosis was 63.3% and chronic thrombosis was 36.7%.Splenomegaly, gastrointestinal haemorrhage, and oesophageal and gastric varices were more common by a statistically significant difference in patients with chronic thrombosis.Ascites was more common in patients with cirrhosis or cancer compared to patients without cirrhosis and cancer.Death occurred in 9 patients, 7 of whom were cancer patients. Conclusion: Portal vein thrombosis is an important condition that has become considered an separate clinical entity, the possible causes and risk factors must be investigated and treated if possible because the prognosis is primarily depended on the underlying cause rather than on the thrombosis and its complications.